Clinical–Educational Qualitative Case Study of Speech Delay in a Four-Year-Old Boy - Ratniawati, Augustina (CV. Chandralia Bintang Pustaka, 2026)
Speech delay in early childhood remains a significant developmental issue that affects children’s communication abilities, social interaction, and school readiness, particularly within clinical and educational contexts where early identification and intervention are often inconsistent. This study aims to explore the characteristics of speech delay in a four-year-old child and to examine how contextual factors and early intervention contribute to language development. A qualitative case study design was employed to provide an in-depth understanding of the child’s communication profile across different settings. Data were collected through clinical and classroom observations, semi-structured interviews with parents and teachers, and document analysis. The data were analyzed using thematic analysis to identify recurring patterns and key themes related to speech and language development. The findings revealed four major themes: expressive language delay, reduced speech intelligibility, contextual variation in communication between clinical and educational settings, and the positive role of parental involvement and early intervention in supporting progress. The study highlights the importance of early identification, family-centered approaches, and integrated clinical–educational collaboration in addressing speech delay. These findings contribute to a deeper understanding of context-sensitive intervention strategies and provide practical implications for educators, clinicians, and policymakers in early childhood education.